Analisis Aktivitas Enzim Peroksidase dan Kandungan Asam Salisilat dalam Tanaman Cabai Merah yang Diinduksi Ketahanannya terhadap Cucumber Mosaic Virus (CMV) oleh Ekstrak Daun Bunga Pukul Empat (Mirabilis jalapa) - Hersanti Hersanti (Jurnal Perlindungan Tanaman Indonesia, 2005)
Leaf crude extract of Mirabilis jalapa is an inducer agent of systemic resistance of red chilli to CMV. This experiment was objected to study the activity of peroxidase enzyme and the concentration of salicylic acid in the induced resistant plant to CMV by M. jalapa leaf crude extract. The results showed that the induced resistant plant to CMV by leaf crude extract of M. jalapa had a low CMV disease intensity, low content of virus, increased the activity of peroxidase enzyme 2 - 10 times; increased the salicylic acid 1.6 - 5 times. There were a significant interaction effect between disease intensity of CMV and salicylic acid content (r = 0.94), middle interaction effect between disease intensity of CMV and salicylic acid content (r = 0.46), low interaction effect between the virus content and disease intensity of CMV (r = 0.32), and salicylic acid and activity of peroxidase enzyme (r = 0.39); and no interaction effect between virus content and salicylic acid content (r = 0.05), and between virus content and activity of peroxidase enzyme ( r = 0.12 ).